Recensiones - Gondra, José María; Achaerandio, Luis; Valero Iglesias, Luis F.; Navarro, Salvador (ECA: Estudios Centroamericanos, 1977)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 32, No. 341, 1977: 258-260.